Decision making in times of Knightian uncertainty: An info-gap perspective - Yakov Ben-Haim; Maria Demertzis (Kiel Institute for the World Economy (IfW), 2015)
The distinction of risk vs uncertainty as made by Knight has important implications for policy selection. Assuming the former when the latter is relevant can lead to wrong decisions. With the aid of a stylized model that describes a bank's decision on how to allocate loans, the authors discuss decision making under Knightian uncertainty. They use the info-gap robust satisficing approach to derive a trade-off between confidence and performance (analogous to confidence intervals in the Bayesian approach but without assignment of probabilities). They show that this trade off can be interpreted as a cost of robustness and that the robustness analysis can lead to a reversal of policy preference from the putative optimum. They then compare this approach to the min-max method which is another main non-probabilistic approach available in the literature.
Keywords: C02; C18; D81; G10; 330; uncertainty vs risk; confidence; robustness; satisficing; info-gap